REVISITING THE LEGALITY OF TRAVEL RESTRICTIONS UNDER INTERNATIONAL LAW DURING COVID-19. Issue 3 (July 2022) - Forman, Lisa; Habibi, Roojin
Abstract: Under the International Health Regulations (IHR), States must consider decision-making criteria in applying travel restrictions during a public health emergency of international concern. Interpretation on the legal parameters of such restrictions varies widely. This article considers whether and how the permissibility of travel restrictions under the IHR may have changed given recent developments, including evolving scientific evidence about their efficacy and shifting World Health Organization (WHO) advice. It is argued that such determinations must conform to the principles of necessity and proportionality as articulated by the IHR, and must also be accompanied by the correlative IHR duties of collaboration and assistance rooted substantively in global solidarity.